Research approach in the Volta Basin Development Challenge not 'business as usual' - Ayantunde, Augustine A. (International Livestock Research Institute, 2011)
In this interview, Augustine Ayantunde from ILRI introduced an ILRI-led project on 'integrated management of rainwater in mixed crop-livestock integrated systems' (in the Volta river basin). The project aims to evaluate and test best fit rainwater management strategies in Ghana and Burkina Faso. According to Ayantunde, the approach of the project is not 'business as usual.' Instead of traditional linear research for farmers, the emphasis project is on the participation of local stakeholders and communities through innovation platforms. The platforms will be mechanisms or spaces where many people involved in a value chain can meet together and collectively design, with the farmers, the right interventions. The Volta Basin Development Challenge is funded by the CGIAR Challenge Program on Water and Food (CPWF).